Adaptation of public health initiatives: expert views on current guidance and opportunities to advance their application and benefit. Issue 4 (6th July 2020) - Yoong, Sze Lin; Bolsewicz, Katarzyna; Grady, Alice; Wyse, Rebecca; Sutherland, Rachel; Hodder, Rebecca Kate; Kingsland, Melanie; Nathan, Nicole; McCrabb, Sam; Bauman, Adrian; Wiggers, John; Moullin, Joanna; et al.
Abstract: While there is some guidance to support the adaptation of evidence-based public health interventions, little is known about adaptation in practice and how to best support public health practitioners in its operationalization. This qualitative study was undertaken with researchers, methodologists, policy makers and practitioners representing public health expert organizations and universities internationally to explore their views on available adaptation frameworks, elicit potential improvements to such guidance, and identify opportunities to improve implementation of public health initiatives. Participants attended a face to face workshop in Newcastle, Australia in October 2018 where World Café and focus group discussions using Appreciative Inquiry were undertaken. A number of limitations with current guidance were reported, including a lack of detail on 'how' to adapt, limited information on adaptation of implementation strategies and a number of structural issues related to the wording and ordering of elements within frameworks. A number of opportunities to advance the field was identified. Finally, a list of overarching principles that could be applied together with existing frameworks was generated and suggested to provide a practical way of supporting adaptation decisions in practice.